A Novel Model for Acute Peripheral Nerve Injury in the Horse and Evaluation of the Effect of Mesenchymal Stromal Cells Applied In Situ on Nerve Regeneration: A Preliminary Study - Cruz Villagrán, Claudia; Schumacher, Jim; Donnell, Robert; Dhar, Madhu S. (Frontiers in Veterinary Science, 2016)
Transplantation of mesenchymal stromal cells (MSCs) to sites of experimentally-created nerve injury in laboratory animals has shown promising results in restoring nerve function. This approach for nerve regeneration has not been reported in horses. In this study, we first evaluated the in vitro ability of equine, bone marrow-derived MSCs (EBM-MSCs) to trans-differentiate into Schwann-like cells (SLCs) and subsequently tested the MSCs, in vivo for their potential to regenerate a transected nerve after implantation. The EBM-MSCs from 3 equine donors were differentiated into SCLs for 7 days, in vitro, in the presence of specialized differentiation medium and evaluated for morphological characteristics, by using confocal microscopy, and for protein characteristics, by using selected Schwann-cell markers (GFAP and S100b). The EBM-MSCs were then implanted into the fascia surrounding the ramus communicans of one fore limb of 3 healthy horses after a portion of this nerve was excised. The excised portion of the nerve was examined histologically at the time of transection, and stumps of the nerve were examined histologically at day 45 after transplantation. The EBM-MSCs from all donors demonstrated morphological and protein characteristics of those of Schwann cells 7 days after differentiation. Nerves implanted with EBM-MSCs after nerve transection did not show evidence of nerve regeneration at day 45. Examination of peripheral nerves collected 45 days after injury and stem cell treatment revealed no histological differences between nerves treated with MSCs and those treated with isotonic saline solution (controls). The optimal delivery of MSCs and the model suitable to study the efficacy of MSCs in nerve regeneration should be investigated.